Gender Differences in Labor Turnover and the Development of Internal Labor Markets in the United States during the 1920s - Owen, Laura J. (Enterprise & Society, 2001)
Exploring the relationship between gender differences in labor turnover—which have been linked to male-female wage differentials—and the early twentieth-century development of internal labor markets, this case study suggests that observed gender differences in labor turnover in the twentieth century can be attributed, at least in part, to the specific employment policy decisions of firms. These policies, and the internal labor markets they helped create, directly addressed some of the causes of male turnover but did little to confront the sources (often non-market) of female turnover. The results of this analysis call into question the assumption that the higher rate of female turnover is exogenously determined.
Keywords: Business History and gender